Inventory management optimization to support integrated logistic operations - Wahyuning Astuti, Iramani; Nizar, Adirizal (The Indonesian Journal of Business Administration, 2016)
Abstract - Nowadays, the healthy lifestyle is becoming popular and most people are consuming the vegetables and fruits in any type either snack, juice drinks, or herbal drinks with nutrition ingredients. The herbal drink is a good business opportunity for PT Morindo International as the beverage manufacture company, with the main raw material is ripened Noni (Morinda Citrifolia), an organic tropical fruit that require long lead time for inventory stock and shall be tight controlled due to easily rotting in the hot season, but should be available anytime to meet target production with on-time delivery. Every manufacture industry focus to the inventory management with target optimization and cost effectiveness. The application of Economic Order Quantity (EOQ) and Reorder Point model as the strategic plan will be used to optimize the inventory management and to support logistics operation. Quantitative resource method with data collection based on fact analysis and combined with qualitative by conducting interview to the knowledge of inventory management, integrated logistics operation for raw material and finished goods, as well as supply chain function. The issues on how the company may handle inventory more effectively to obtain the optimal order quantity, with sufficient number of safety stock to consider the noni fruit lead time and the production cost more efficiently. In conclusion that company has the right answer how many quantity order, when to reorder and how much the cost.Keywords: Inventory management, Logistic operations, Supply chain functionÂ Â